Murder is easy - Christie, Agatha, 1890-1976. (New York : HarperPaperbacks, 1992)
Fitzwilliam, recently retired from a police career in Asia, meets a lady on a train to London and dismisses her talk of murder as nonsense until he reads of her death in the paper the next morning.
Previous ed. published in 1939 as: Easy to kill / Agatha Christie.
Young Adult
Keywords: Murder -- England -- Fiction; Homicide -- Fiction; Mystery fiction; England -- Fiction; England -- Fiction; Detective and mystery stories